Kesehatan Mental Remaja Dalam Penggunaan Gadget - Putri, Lydia Mardison; Febrina, Cory; Mariyana, Rina (REAL in Nursing Journal, 2022)
Background: Teenagers cannot survive without gadgets. Teenagers today are a generatbehavior in adolescents due to the use of gadgets is an urgent problem, this is caused because ion that cannot survive without gadgets, laptops, and cell phones for a minute. The use of gadgets causes dependence, one of the impacts that arise is violent behavior through social media. Gadget dependence in adolescence is a small part of the population, but has a very large contribution. This study aims to look at the characteristics of adolescents as gadget users, duration of use, applications that are widely used and the distribution of mental health of teenagers who use gadgets. Methods: This study uses a quantitative design. The research was conducted in West Sumatra. Children are given a questionnaire and fill out related to how the individual's mental response in using gadgets. The data were then analyzed using descriptive methods. Results: This study resulted in 273 respondents, 3.7% of respondents experienced delays in completing activities according to plan, 11.4% of respondents experienced a lack of concentration in learning, 20.2% of respondents experienced feelings of emptiness without gadgets, 11% experienced feelings of dependence on friends at school. virtual world than friends in the real world, 17.2 states that they never miss the latest news through gadgets, 10.6% of respondents feel angry when they are cannot used gadgets. Conclusion: This research shows that teenagers experience a variety of responses that they cannot control. Therefore, it is very important for families to set limits on the use of gadgets by limiting the duration of gadget use, increasing physical activity and returning children to the real world.